Peningkatan Keterampilan Berbicara Bahasa Inggris Menggunakan Model Pembelajaran Multiliterasi di SMAN 5 Kabupaten Halmahera Utara - Samsi, Aderawan Ade (Jurnal Ilmiah Wahana Pendidikan, 2023)
This classroom action research started from the problem of learning English speaking skills as uninteresting and monotonous. This causes student learning outcomes in these skills to be very low. Therefore, to support the successful achievement of learning English speaking skills, teachers need adequate innovative learning models. This classroom action research aims to improve the English speaking skills of class XI students at SMAN 5 North Halmahera Regency. This classroom action research uses a model developed by Kemmis and Mc. Taggart. This classroom action research was carried out in two cycles. Each cycle consists of planning stages, observation actions, and action reflection. Data analysis in this action research uses simple statistics, namely descriptive analysis. Descriptive analysis is an analysis model by comparing the average percentages. Based on data analysis, it was found that in cycle I it was 48% and in cycle II it increased to 92%. The results of observations from cycle I on teacher activity reached 71% and student activity reached 62.5%. In cycle II, teacher activity increased by 89% and student activity also reached 89%. Thus, the use of the multiliteracy learning model can improve the English speaking skills of class XI students at SMAN 5 North Halmahera Regency.